2007
DOI: 10.3793/jaam.4.43
|View full text |Cite
|
Sign up to set email alerts
|

Association of Personality (NEO-Five Factor Inventory) with Eating Behaviors and Physical Activity Levels in Obese Subjects in the Saku Control Obesity Program (SCOP)

Abstract: BACKGROUND:Obesity is one of the most common risks for lifestyle-related diseases, but the personality of individuals in relation to obesity has not been well studied. We investigated the association of personality traits with physical activity levels and eating behaviors in obese subjects. METHOD: The subjects were 116 males and 119 females in the Saku Control Obesity Program SCOP study. The influence of personality on obesity was analyzed using a questionnaire from the NEO-FFI. We analyzed the association of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 9 publications
3
15
1
Order By: Relevance
“…In line with the literature [12][13][14], extraversion had a positive association with self-reported physical activity among middle-aged women. Furthermore, as in previous studies among college women [19], obese middle-aged adults [18] and older adults [21], extraversion was not associated with accelerometer-measured physical activity. It is possible that people high in extraversion tend to give socially desirable responses to self-reports [19].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In line with the literature [12][13][14], extraversion had a positive association with self-reported physical activity among middle-aged women. Furthermore, as in previous studies among college women [19], obese middle-aged adults [18] and older adults [21], extraversion was not associated with accelerometer-measured physical activity. It is possible that people high in extraversion tend to give socially desirable responses to self-reports [19].…”
Section: Discussionsupporting
confidence: 74%
“…This is important, especially among older adults whose daily activity is mainly light intensity [17]. Accelerometer studies have not reported consistent associations with personality traits [18][19][20][21][22]. This may be due to relatively small sample sizes and the use of convenience samples of active older adults (n = 69) [20], obese middle-aged men and women (n = 235) [18], college women (n = 294) [19] and young men and women (n = 64) [22].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, 56 were excluded from the analysis because of missing data (age (n=2), current work schedules (n=6), residential status (n=1), marital status (n=2), years of experience as a rotating shift worker (n=23), smoking status (n=2), alcohol status (n=4), number of night shifts during the previous month (n=6) and the questionnaire about diurnal preference (n=13)). Since the scoring method for the questionnaire about obesity-related eating behaviour was different for men and women,23 24 we decided to exclude the small data from male nurses (n=20). As a result, 162 female nurses (39-day workers and 123 shift workers) were analysed (figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Such measures also have no method overlap with personality assessment. The few studies that have used objective measures of PA, however, have relied on select and younger populations to assess the relation between personality and PA. Ohmori et al (2007) examined the link between PA measured by accelerometers in Japanese middle-aged individuals who were part of a behavioral intervention for obesity and found that females who were low in Neuroticism had lower step counts and PA levels. Wilson et al (2015) also assessed PA using accelerometers in young women.…”
mentioning
confidence: 99%